2020
DOI: 10.3390/su12145866
|View full text |Cite
|
Sign up to set email alerts
|

Examining Fractional Vegetation Cover Dynamics in Response to Climate from 1982 to 2015 in the Amur River Basin for SDG 13

Abstract: The impacts of climate and the need to improve resilience to current and possible future climate are highlighted in the UN’s Sustainable Development Goal (SDG) 13. Vegetation in the Amur River Basin (ARB), lying in the middle and high latitudes and being one of the 10 largest basins worldwide, plays an important role in the regional carbon cycle but is vulnerable to climate change. Based on GIMMS NDVI3g and CRU TS4.01 climate data, this study investigated the spatiotemporal patterns of fractional vegetation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Meteorological data are used to simulate landscape functions, where precipitation, temperature, and potential evapotranspiration data are available in the National Earth System Science Data Center, National Science & Technology Infrastructure of China. The solar radiation data are developed by interpolating from weather station data [30]. Simulate water yield 100 m Team-made 3 Normalized vegetation index Simulate water yield Simulate carbon sequestration 100 m Team-made 4…”
Section: Data Collectionmentioning
confidence: 99%
“…Meteorological data are used to simulate landscape functions, where precipitation, temperature, and potential evapotranspiration data are available in the National Earth System Science Data Center, National Science & Technology Infrastructure of China. The solar radiation data are developed by interpolating from weather station data [30]. Simulate water yield 100 m Team-made 3 Normalized vegetation index Simulate water yield Simulate carbon sequestration 100 m Team-made 4…”
Section: Data Collectionmentioning
confidence: 99%
“…The FVC classification was based on previous studies combined with the actual situation of the basin to determine the classification boundaries [29,31]. The area with FVC ≤ 10% was classified as "Bare soil or non-vegetation", while 30, 45, and 60% were the upper limit of the status of coverage and were classified as "Low", "Low-medium", and "Medium", respectively.…”
Section: Calculation and Classification Of Fvcmentioning
confidence: 99%
“…As the largest river basin in Northeast Asia, the Heilongjiang River connects 15 firstlevel administrative regions across China, Mongolia, Russia, and North Korea. Changes in its internal resources and environment have a major impact on the green development of the China-Mongolia-Russia Economic Corridor (CMREC) [27][28][29]. Approximately 48% of the river basin lies in China, which covers the entire Heilongjiang Province and parts of Jilin Province and Inner Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…As a key variable, FVC has been widely used for agricultural yield prediction, ecological monitoring, and drought assessment [21][22][23]. In this context, Yang et al [24] indicated that FVC depicts increasing trends in the growing season and insignificant increasing trends in summer, while in some cases, a significant decrease is observed in the growing season. Mu et al [25] used the Global Land Surface Satellite (GLASS) to investigate the FVC trend in major Chinese cities and quantify CO 2 concentrations caused by urbanization [26].…”
Section: Introductionmentioning
confidence: 99%